Electric field strength on water based aluminum alloys nanofluids flow up a non-linear inclined sheet - Kandasamy, Ramasamy; Adnan, Nur Atikah; Abbood, Jaafar Abdul Abbas; Kamarulzaki, Mohd; Rusiman, Mohd Saifullah (Elsevier, 2019)
Nanoparticle shapes on radiative MHD water based aluminum alloy nanoparticles, AA7072 and AA7075 flow up a non-linear wall with distinct flow condition is analyzed. The three absolute pattern of nanoparticle shapes is enlisted into transcript, i.e. cylinder, sphere and lamina. The system of equations (ODEs) is resolved generally by running R.K Fehlberg method, MAPLE 18. Thermal energy film of the sphere shape particles of AA7075 – water is notably higher than another configuration in the flow regime.